Financial Technology Adoption in Public Financial Management of South Africa: a Path Toward Digital Transformation - Enwereji, Prince Chukwuneme; Stofile, Regina (Indonesian Journal of Information Systems, 2026)
This study examines the adoption of Financial Technology in South African public sector financial management. The study adopted a qualitative research approach and depended on literature reviews for data collection. A total of 260 articles were downloaded for this study while only 11 articles were used after rigorous selection criteria. The findings show that mobile payments and digital banking have significantly improved financial inclusion, especially in urban areas, although adoption in rural regions has been slower due to challenges such as poor infrastructure and low digital literacy. More advanced FinTech solutions, like blockchain and Artificial Intelligence, are still in early stages. The adoption of FinTech has led to greater efficiency in government financial processes, automating tasks like payments and tax filings, which has reduced manual workloads and sped up service delivery. Blockchain technology has improved transparency and accountability and has allowed for better tracking of public funds and reducing the risk of fraud. However, the full potential of FinTech has been limited by barriers like outdated infrastructure, regulatory gaps, and resistance to change within the public sector. To unlock the full potential of FinTech, the study recommends among others, improving digital infrastructure, enhancing digital literacy, and strengthening regulatory frameworks. Keywords: Financial technology, Public financial management, Blockchain technology, Digital transformation, Financial inclusion, Digital financial services